IDENTIFICATION OF AMPC Î’-LACTAMASE-PRODUCING CLINICAL ISOLATES OF ESCHERICHIA COLI - Gupta, Tanushree B; Shariff, Malini; Ss, Thukral; SS, THUKRAL (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Indiscriminate use of Î²-lactam antibiotics has resulted in the emergence of Î²-lactamase enzymes. AmpC Î²-lactamases, in particular, confer resistance to penicillin, first-, second-, and third-generation cephalosporins as well as monobactams and are responsible for antibiotic resistance in nosocomial pathogens. Therefore, this study was undertaken to screen nosocomial Escherichia coli isolates for the presence and characterization of AmpC Î²-lactamases. The study also envisaged on the detection of inducible AmpC Î²-lactamases and extended-spectrum Î²-lactamases (ESBLs) in AmpC Î²-lactamase-producing E. coli. Methods: A total of 102 clinical isolates of E. coli, were subjected to cefoxitin screening, and screen-positive isolates were further subjected to inhibitor-based detection method, phenotypic confirmatory test, disc antagonism test, polymerase chain reaction (PCR), and isoelectric focusing (IEF). Results: In this study, 33% of E. coli were resistant to cefoxitin, of which 35% were found to be positive for AmpC Î²-lactamase by inhibitor-based phenotypic test. Of the AmpC-positive isolates, 83% were positive for ESBLs, whereas 25% were producing inducible AmpC Î²-lactamases. PCR and IEF showed CIT and EBC types of AmpC Î²-lactamases present in the tested isolates. Conclusion: Our study showed the presence of inducible AmpC enzymes and ESBLs in E. coli isolates and PCR identified more isolates to be AmpC producers.